EARTH ALIVE IN ART AND SYMBOLISM - Kattukaran, Paul (Journal of Dharma, 1993)
Religion which grew in an essentialistic tradition of thinking is facing unprecedented crisis and is seeking to renew itself by embracing the very ancient existentialist attitude to life. The essentialistic orientation to life tries to exclude new possible understanding of reality and emergent life-styles, and being totalitarian in its approach, it dominates and subdues what is earthly and bodily in human existence. Today the essentialist fortress of organised religion is showing serious cracks and the faithful, the people of God who nurture faith, are coming home to their original and existential life-springs of body. If we speak in terms of the phenomenon of consciousness, the human being •is becoming aware of himself as the anima/ symbolicum or rather as the 'religious animal'.